2009
DOI: 10.1186/1475-2875-8-174
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of malaria from monotherapy to artemisinin-based combination therapy by health professionals in rural health facilities in southern Cameroon

Abstract: Background: One year after the adoption of artesunate-amodiaquine (AS/AQ) as first-line therapy for the treatment of uncomplicated malaria, this study was designed to assess the treatment practices regarding anti-malarial drugs at health facilities in four rural areas in southern Cameroon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 6 publications
2
23
0
Order By: Relevance
“…The results of this study show an improvement of the situation in Cameroon in 2005, when prescribing records indicated that less than 15% of antimalarials prescribed were an ACT (Sayang et al. 2009b,c).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The results of this study show an improvement of the situation in Cameroon in 2005, when prescribing records indicated that less than 15% of antimalarials prescribed were an ACT (Sayang et al. 2009b,c).…”
Section: Discussionmentioning
confidence: 80%
“…2009b,c). The use of quinine in non‐severe cases has fallen substantially since 2005 (Sayang et al. 2009b,c); though, it remains a concern: 16% of patients with symptoms of uncomplicated malaria were prescribed or received quinine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cameroon, quinine has continued to be used as first-line therapy, with 45% of adults receiving oral quinine for uncomplicated malaria. 78 Recent surveillance data from sentinel sites in Uganda showed that quinine was prescribed for up to 90% of children younger than age 5 years with uncomplicated malaria. 79 Furthermore, this drug and its analogs are widely distributed to healthy children as preventive treatment (prophylaxis campaigns).…”
Section: Gene Polymorphisms and Risk For Ksmentioning
confidence: 99%
“…[13] At present, many pathogens mutate and become resistant to medication, so search for new agents (more destructive for a given pathogen) is still continuing. [14] New, effective agents against malaria are still among the most needed medicines. At times when most strains of Plasmodium have become resistant to currently used drugs, this type of research is particularly important and justified.…”
Section: Introductionmentioning
confidence: 99%